Single-centre experience: Comparing recurrence rates and clinical characteristics in atrial fibrillation patients undergoing wide-area circumferential ablation (WACA) versus WACA plus adjunctive ablation - Chiang, Kit Hou; Andy Tze Yang, Ko; Koh, Keng Tat; Ho, Kian Hui; Leong, Lai Kuan; Chung, Bui Khiong; Ling, Hwei Sung; Julian Wei Ee, Tong; Esteban Yu Hern, Chin; Cheng Foong, Cheah; Khor, How Kiat; Pang, Ing Xiang; et al. (Elsevier B.V., 2024)
Catheter ablation has emerged as effective therapy for patients with symptomatic atrial fibrillation (AF), especially in those refractory or intolerants to medical therapy. Conventional technique used is wide area circumferential ablation (WACA). Adjunctive ablation techniques such as performing additional linear lesion or targeting complex fractionated atrial electrogram (CFAE) are still area of ongoing research. There is least amount of literature in this area published in Malaysia.